A clinical study of prevalence of ocular manifestations in malnourished children attending Anganwadi centers in urban slum areas - Priti Singh; Rashmi Kumar; Swarna Das (International Journal of Medical Research and Review, 2017)
Aim: A clinical study of prevalence of ocular manifestations in malnourished children attending anganwadi centers in urban slum areas.Material & Method: A cross sectional study was carried out in Anganwadi centers of urban slum area, with children of age group 0 – 6 years. All children underwent detailed systemic and ocular examination and were graded for malnutrition according to IAP classification. The results were analysed statistically.Results: In our study the prevalence of ocular manifestations is 9.6% (50). Prevalence of malnutrition is 18.53% (96). Out of 96 malnourished, 56 children (58.33%) belong to grade I malnutrition, out of which 16 children (32%) had ocular manifestation, which is total ocular manifestation in all the grades of malnutrition. So, ocular manifestation in malnourished children is 32%. Overall ocular involvement was seen in 50 children out of 518 children examined, with overall prevalence of 9.65%. Thereis significant difference of ocular involvement between malnourished and wellnourished (p value – 0.017).Conclusion: Overall prevalence of malnourished children wasfound to be very less at anganwadi centers in our study. This may be probably due to the timely vaccination of children and the nutritional supplements being provided to them at Anganwadi centers through various national programmes.